Boosting Him but Not Her: Negative Stereotypes and Leader–Follower Relations - Czukor, Gergely; O’Brien, Anne; Pye, Annie (Springer Science and Business Media Deutschland GmbH, 2024)
This study investigated how situational negative stereotypical expectations about men or women affected followers’ evaluations of their male or female leaders representing their teams in an inter-team context. Undergraduate students enrolled in a leadership course participated in two experiments for experiential learning as part of non-graded in-class course activity. The study used a cross-sectional experimental design with gender stereotype condition (experiment 1: advantage or disadvantage; experiment 2: advantage or control) and leader gender (male or female) as independent variables and followers’ ratings for their team-leaders as the dependent variable. The teams were randomly assigned to the conditions. Prior to the leaders’ performances (experiment 1: giving an oral presentation; experiment 2: participating in a committee meeting), the followers read stereotype manipulations targeting the gender of their leader and then rated their leaders’ communication effectiveness (experiment 1) or representation effectiveness (experiment 2). Followers evaluated male leaders more favorably when males were expected to underperform females, relative to a male stereotype advantage (experiment 1, d =.90) or control condition (experiment 2, d =.87). The ratings for female leaders were not different between the experimental and the comparative conditions. Negative stereotyping seemed to mobilize followers to show solidarity with male leaders, but there was a lack of vigor to show support for female leaders. The study enhances the criterion validity of the stereotype threat construct in leadership by extending outcomes to leader–follower relations, using stereotype salience manipulations. To mitigate consequences of the situational salience of stereotypes, interventions should focus on enhancing follower support for female leaders. © Associação Brasileira de Psicologia 2024.
Keywords: Collective Threat; Communication Effectiveness; Female Leaders; Leader Representation Effectiveness; Stereotype Threat; Stereotyping